Pax1a-EphrinB2a pathway in the first pharyngeal pouch controls hyomandibular plate formation by promoting chondrocyte formation in zebrafish - Jeon, Haewon; Jin, Sil; Kim, Jihyeon; Joo, Saehoon; Choe, Chong Pyo (Frontiers in Cell and Developmental Biology, 2025)
The hyomandibular (HM) cartilage securing the lower jaw to the neurocranium in fish is a craniofacial skeletal element whose shape and function have changed dramatically in vertebrate evolution, yet the genetic mechanisms shaping this cartilage are less understood. Using mutants and rescue experiments in zebrafish, we reveal a previously unappreciated role of Pax1a in the anterior HM plate formation through EphrinB2a. During craniofacial development, pax1a is expressed in the pharyngeal endoderm from the pharyngeal segmentation stage to chondrocyte formation. Loss of pax1a leads to defects in the first pouch and to the absence of chondrocytes in the anterior region of the HM plate caused by increased cell death in differentiating osteochondral progenitors. In pax1 mutants, a forced expression of pax1a by the heat shock before pouch formation rescues the defects in the first pouch and HM plate together, whereas a forced expression of pax1a after pouch formation rescues only the defects in the HM plate without rescuing the first pouch defects. In pax1a mutants, ephrinb2a expressed in the first pouch is downregulated when adjacent osteochondral progenitors differentiate into the chondrocytes, with mutations in ephrinb2a causing hyomandibular plate defects. Lastly, pax1 mutants rescue the anterior hyomandibular plate defects by pouch-specific restoration of EphrinB2a or a heat-shock-treated expression of ephrinb2a after pouch formation. We propose that the Pax1a-EphrinB2a pathway in the first pouch is directly required to shape the HM plate in addition to the early role of Pax1a in the first pouch formation.